2010
DOI: 10.1093/rpd/ncq238
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary indoor thoron measurements in high radiation background area of southeastern coastal Orissa, India

Abstract: This paper presents the preliminary results of radon and thoron measurements in the houses of Chhatrapur area of southeastern coast of Orissa, India. This area is one of the high radiation background radiation areas in India, which consists of monazite sand as the source of thoron. Both active and passive methods were employed for the measurements. Radon and thoron concentrations were measured in the houses of Chhatrapur area using twin cup radon dosemeters, RAD7 and radon-thoron discriminative detector (Radue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…The thickness of the films was adjusted to absorb the energy of alpha particles from radon, thoron and their progenies except for 212 Po (8.78 MeV). Since the Raduet and thoron progeny deposition detector are inexpensive and easy to use, they are often used in a large-scale survey (e.g., Chen et al, 2012;Janik et al, 2013;Kudo et al, 2015;McLaughlin et al, 2011;Ramola et al, 2010Ramola et al, , 2012.…”
Section: Measurement Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness of the films was adjusted to absorb the energy of alpha particles from radon, thoron and their progenies except for 212 Po (8.78 MeV). Since the Raduet and thoron progeny deposition detector are inexpensive and easy to use, they are often used in a large-scale survey (e.g., Chen et al, 2012;Janik et al, 2013;Kudo et al, 2015;McLaughlin et al, 2011;Ramola et al, 2010Ramola et al, , 2012.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…In this area, surveys on radon and thoron concentrations in dwellings were carried out and they revealed that thoron concentration is higher than radon concentration (e.g., Ramola et al, 2010Ramola et al, , 2012Sulekha Rao and Sengupta, 2010). Sulekha Rao and Sengupta (2010) also attempted to calculate the dose due to inhalation of thoron (including its progeny) based on measurements of thoron gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, Rn studies were more common than those of Tn, but recent studies in Serbian [13], Chinese [4, 5], Indian [6] Canadian [79], Japanese [10], Korean [11, 12], Hungarian [13], Slovenian [14], Irish [15, 16] and USA [17] dwellings have show that Tn can be a significant contributor to the radiation exposure. The contributions of Rn and Tn and its progeny (TnP) to radiation exposure are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Since the hypothesis of hormesis was reported in 1982 by Luckey, people have had some new understand on this problem Ramola et al, 2010Ramola et al, , 2012Walsh & Kaiser, 2011;Rautela et al, 2012). The epidemiology showed that the incidence of tumor was not increased in those people who were workers in A-test place, victims receiving low dose radiation in explosion of atom-bomb and atomic accidents, medical staff in radiology department and patients receiving radiation treatment.…”
Section: Introductionmentioning
confidence: 99%